Hyperspectral volumetric coherent anti‐Stokes Raman scattering microscopy: quantitative volume determination and NaCl as non‐resonant standard. (10th February 2016) - Karuna, Arnica; Masia, Francesco; Borri, Paola; Langbein, Wolfgang
Abstract : In this work, we demonstrate quantitative volume determination of chemical components in three dimensions using hyperspectral coherent anti‐Stokes Raman scattering microscopy, phase‐corrected Kramers–Kronig retrieval of the coherent anti‐Stokes Raman scattering susceptibility and factorization into concentration of chemical components. We investigate the influence of the refractive index contrast between water and polymer beads (polystyrene and polymethylmethacrylate), showing that it leads mainly to concentration errors, while the spectral error is less affected. The volume of polystyrene beads of sizes from 200 nm to 3  μ m is determined with 10% relative error and 1% absolute error in the region of interest. We furthermore establish the use of sodium chloride as non‐resonant reference material free of Raman‐active vibrational resonances. © 2016 The Authors Journal of Raman Spectroscopy Published by John Wiley & Sons Ltd. Abstract : Hyperspectral coherent anti‐Stokes Raman scattering (CARS) microscopy is a fundamental tool in cell biology due to the ability to map the concentration of the endogenous molecules in cells with superior chemical specificity. Here we demonstrate the applicability of our hyperspectral CARS image analysis method for quantitative determination of the absolute volumes of chemical components in three‐dimensional imaging. Additionally, we discuss the use of sodiumchloride as a standard non‐resonant referencematerial for CARS alternative to commonly used glass.